SUPERVISION OF THE CONSUMER DISPUTE SETTLEMENT AGENCY ON THE INCLUSION OF STANDARD CLAUSE AGREEMENTS THAT HARM CONSUMERS - Nofiyanti, Dwi; Yuhelson, Yuhelson; Darodjat, Tubagus Achmad (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
The inclusion of standard clauses that harm consumers is still rampant in various sectors of trade in goods and services in Indonesia. The Consumer Dispute Settlement Agency (CDSA) has an important mandate to supervise and resolve consumer disputes, including assessing the existence of unfair standard clauses. This study aims to analyze the effectiveness of CDSA’s supervision of agreements that include unfair standard clauses, as well as assess the challenges of implementing this role in practice. This research uses a juridical-empirical approach with case studies on several CDSA decisions in Indonesia. The findings show that there are institutional weaknesses and inconsistencies in the decisions that make the role of CDSA not optimal. This article offers strategies to strengthen the regulation and role of CDSA to protect consumer rights more effectively.